Filsafat Rasionalisme Sebagai Dasar Ilmu Pengetahuan - Nurkaidah; Bahar, Herwina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Rationalism is a school of thought in philosophy that holds that, in order to gain and share information, reason and ratio must predominate. Logic and intelligence, according to rationalists, are the means by which one may acquire knowledge. The guiding philosophical principles that laid the groundwork for scientific inquiry are the focus of this investigation. Library research is the method used in this study. Knowledge is captured and discovered by humans via the use of their intellect. There can be no truth based on a lie, according to the rationalist school of thought, since God has given humanity the ability to reason and not to lie. The rationalist position holds that all knowledge is derived from reasoning or the ratio. This is where science starts, and ultimately, modern sciences like mathematics are born out of the philosophy of rationalism. Since these fields are universally acknowledged as having ultimate truth, it follows that rationalism is a fundamental truth that gives rise to science through the study of ratios and reason.